Identification of hazards and risk assessment for a 40kVA diesel powered lighting set. - Olabiyi, B.A.; Adegbola, A.A.; Kolawole, P., (2012)
The process of installing, operating and maintaining power sets carries with them occupational hazards, the hazards and risks associated with installation, operation and maintenance of diesel powered generator using a 40kVA generator was identified. The findings reveal that five major jobs or tasks were associated with the events of installation, operation and maintenance of any typical industrial standby generator. Hazards of varying degrees were identified with every section and jobbing of the whole activities. The associated risk was classification, about 60 percent high risk to 40 percent medium risk. The most hazardous tasks include, engine operation, electrical wiring and connection to the generator. The receipt and installation of the generator with preparation of foundation and engine maintenance were identified.